Caregiving at the margins: An ethnographic exploration of family caregivers experiences providing care for structurally vulnerable populations at the end-of-life. (July 2020) - Stajduhar, Kelli I; Giesbrecht, Melissa; Mollison, Ashley; Dosani, Naheed; McNeil, Ryan
Background: People experiencing structural vulnerability (e.g. homelessness, poverty, racism, criminalization of illicit drug use and mental health stigma) face significant barriers to accessing care at the end-of-life. 'Family' caregivers have the potential to play critical roles in providing care to these populations, yet little is known regarding 'who' caregivers are in this context and what their experiences may be. Aim: To describe family caregiving in the context of structural vulnerability, to understand who these caregivers are, and the unique challenges, burdens and barriers they face. Design: Critical ethnography. Setting/participants: Twenty-five family caregivers participated. Observational fieldnotes and semi-structured interviews were conducted in home, shelter, transitional housing, clinic, hospital, palliative care unit, community-based service centre and outdoor settings. Results: Family caregivers were found to be living within the constraints of structural vulnerability themselves, with almost half being street family or friends. The type of care provided varied greatly and included tasks associated with meeting the needs of basic survival (e.g. finding food and shelter). Thematic analysis revealed three core themes regarding experiences: Caregiving in the context of (1) poverty and substance use; (2) housing instability and (3) challenging relationships. Conclusion: Findings offer novel insight into the experiences of family caregiving in the context of structural vulnerability. Engaging with family caregivers emerged as a missing and necessary palliative care practice, confirming the need to re-evaluate palliative care models and acknowledge issues of trust to create culturally relevant approaches for successful interventions. More research examining how 'family' is defined in this context is needed.